Can positional MRI predict dynamic changes in the medial plantar arch? An exploratory pilot study. Issue 1 (December 2016) - Johannsen, Finn; Hansen, Philip; Stallknecht, Sandra; Rathleff, Michael; Hangaard, Stine; Nybing, Janus; Boesen, Mikael
Abstract Background Positional MRI (pMRI) allows for three-dimensional visual assessment of navicular position. In this exploratory pilot study pMRI was validated against a stretch sensor device, which measures movement of the medial plantar arch. We hypothesized that a combined pMRI measure incorporating both vertical and medial displacement of the navicular bone induced by loading would be correlated with corresponding stretch sensor measurements. Methods 10 voluntary participants were included in the study. Both pMRI and subsequent stretch sensor measurements were performed in a) supine, b) standing and c) standing position with addition of 10 % body weight during static loading of the foot. Stretch sensor measurements were also performed during barefoot walking. Results The total change in navicular position measured by pMRI was 10.3 mm (CI: 7.0 to 13.5 mm). No further displacement occurred when adding 10 % bodyweight (mean difference: 0.7 mm (CI: −0.7 to 2.0 mm), P  = 0.29). The total navicular displacement correlated with stretch sensor measurement under static loading conditions (Spearman's rho = 0.66, P  = 0.04) but not with measurements during walking (Spearman's rho = 0.58, P  = 0.08). Conclusions Total navicular bone displacements determined by pMRI showed concurrent validity with stretch sensor measurements but only so under static loading conditions. Although assessment of total navicular displacement by combining concomitant vertical and medial navicular bone movements would appear advantageous compared to monoplanar measurement the combined measure did not seem to predict dynamic changes of the medial foot arch during walking, which are among several possible factors depending on different walking patterns.